STUDENTS' SPEAKING PROFICIENCY AND SELF-ASSURANCE IN PROMOTING PALEMBANG CITY TOURISM - Qorry Pramesti Regita Cahyani; Hermansyah; Aswadi Jaya (Universitas PGRI Palembang, 2024)
The primary focus of the research were to the implementation of the Project-Based Learning (PBL) strategy to increase students' speaking achievement and self-confidence at Universitas PGRI Palembang as the effort in promoting the tourism of Palembang city. How could Project-Based Learning strategy affect the speaking achievement and self-confidence of the students at Universitas PGRI Palembang as the effort in promoting the tourism of Palembang city. The areas of speaking that needed improvement were pronunciation, grammar, vocabulary, comprehension, and fluency. The use of project-based learning had been found to be effective in enhancing students' speaking abilities, since it fosters positive attitudes towards English language learning, particularly in speaking domains. This would allow them to deal with subjects and communicate thoughts using the suitable range and flexibility of speaking and based on the analysis of the data, the students’ speaking achievement and self-confidence of the English Education at fourth semester students at Universitas PGRI Palembang was in high level.